1990
DOI: 10.1093/schbul/16.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Drug Abuse in Schizophrenic Patients: Clinical Observations and Patients' Self-reports

Abstract: Substance abuse among schizophrenic patients is an increasingly recognized clinical phenomenon. The authors review experimental and observed clinical effects of drug abuse and patients' subjective experiences of acute intoxication. Though drug abuse may exacerbate psychotic symptoms, abused drugs may also lead to transient symptom reduction in subgroups of schizophrenic patients. Some patients report feeling less dysphoric, less anxious, and more energetic while intoxicated. Models of the relationship of drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
0
7

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(122 citation statements)
references
References 68 publications
8
107
0
7
Order By: Relevance
“…53 Substance abuse may exacerbate psychotic symptoms, and abused drugs may also lead to transient symptom reduction. 54 However, some studies report no association between substance abuse and relapse. 55 It must be emphasised nevertheless that although it is not clear that substance abuse in patients with schizophrenia results in relapse, it does lead to inter alia increased psychosocial problems, infections, sexually risky behaviour, and hostile and disorganised behaviour -and more so in the presence of other health-related problems, poverty, insufficient food, poor housing and widespread unemployment.…”
Section: Substance Abusementioning
confidence: 99%
“…53 Substance abuse may exacerbate psychotic symptoms, and abused drugs may also lead to transient symptom reduction. 54 However, some studies report no association between substance abuse and relapse. 55 It must be emphasised nevertheless that although it is not clear that substance abuse in patients with schizophrenia results in relapse, it does lead to inter alia increased psychosocial problems, infections, sexually risky behaviour, and hostile and disorganised behaviour -and more so in the presence of other health-related problems, poverty, insufficient food, poor housing and widespread unemployment.…”
Section: Substance Abusementioning
confidence: 99%
“…However, Schneier and Siris (1987) and Dixon, Haas, Weiden, Sweeney, and Francis (1990) suggested that patients may use these substances to counteract negative symptoms or the effects of neuroleptic medications. The conclusions by Mueser et al (1990) and Schneier and Siris (1987) concerning alcohol use appear in direct contrast to the epidemiological data of Regier et al (1990) , which indicate that schizophrenic individuals abuse alcohol more than the general population.…”
mentioning
confidence: 99%
“…L'impact de l'a bus de sub stan ces sur la ré ponse au trai te ment phar ma co lo gique et l'é vo lu tion de la ma la die est très peu do cu menté. Peu d'in té rêt a été porté au po ten tiel d'in te rac tion entre l'a bus de sub stan ces et la ré -ponse au trai te ment phar ma co lo gi que (Buckley et al, 1994 ;Dixon et al, 1990). Pour tant, plu sieurs sub stan ces in ter agis sent de fa çon complexe avec les symp tô mes et les pro blè mes as so ciés à la schi zo phré nie ) ou en core avec les mé di ca ments uti li sés dans le trai te ment de cette ma la die (Liberman and Bowers, 1990).…”
Section: Ap Pro Che Phar Ma Co Lo Gi Queunclassified